Exploring the Design Space of AAC Awareness Displays - Sobel, Kiley; Fiannaca, Alex; Campbell, Jon; Kulkarni, Harish S.; Paradiso, Ann; Cutrell, Ed; Morris, Meredith Ringel (Proceedings of CHI 2017, 2017)
Augmentative and alternative communication (AAC) devices are a critical technology for people with disabilities that affect their speech. One challenge with AAC systems is their inability to portray aspects of nonverbal communication that typically accent, complement, regulate, or substitute for verbal speech. In this paper, we explore the design space of awareness displays that can supplement AAC devices, considering their output features and their effects on the perceptions of interlocutors. Through designing prototypes and getting feedback on our designs from people with ALS, their primary caregivers, and other communication partners, we consider (1) the consistent tensions that arose between abstractness and clarity in meaning for these designs and (2) the ways in which these designs can further mark users as “other.” Overall, we contribute a generative understanding of designing AAC awareness displays to augment and contextualize communication.
Best Paper Honorable Mention